Ce-promoted highly active bifunctional Pd/Al2O3 catalyst for reversible catalytic hydrogenation and dehydrogenation of N-propylcarbazole. (1st January 2023) - Li, Chenggen; Zhang, Qingyang; Xu, Zhenggang; Liu, Li; Zhu, Ting; Chen, Zhiwen; Dong, Yuan; Yang, Ming
Abstract: In this work, we prepared highly dispersed CeO2 nanoparticle-modified Pd/Al2 O3 catalyst and applied it for the reversible hydrogenation and dehydrogenation of N-propylcarbazole. Compared with the commercially available 1 wt% Pd/Al2 O3 catalyst, the catalyst Pd/CeAl-20 exhibited better catalytic performance, realizing the full hydrogenation of N-propylcarbazole and the full dehydrogenation of perhydro-N-propylcarbazole within 180 min. Thus, it shows excellent commercial potential in large-scale applications. XRD and CO pulse chemisorption results indicated that CeO2 improved the dispersion of Pd nanoparticles on the support surface. H2 -TPR measurements indicated that CeO2 weakened the strong interaction between the Pd particles and the support, inhibiting the formation of stable PdO. HRTEM images and XPS spectroscopic analysis show an apparent electronic transfer between Pd and CeO2 at the Pd–CeO2 interface. The formed Pd–O–Ce structure modulates the electronic state of the Pd particles, which contributes to the excellent catalytic performance of the Pd/CeAl-20 catalyst. This study reveals the crucial role of the combined promotion of the size of the active site and the chemical microenvironment for the reversible hydrogenation and dehydrogenation of N-heterocycles. Graphical abstract: Image 1 Highlights: A Ce-promoted highly active bifunctional Pd/Al2 O3 catalyst was introduced. The catalyst was synthesized by co-precipitation method with supercritical drying. Pd/CeAl-20 shows excellent activity for both hydrogenation and dehydrogenation. The formed Pd–O–Ce structure modulates the electronic state of the Pd particles. The Pd/CeAl-20 catalyst is very promising for application in LOHC technology.